Factors affecting milk cortisol in mid lactating dairy cows. Issue 1 (December 2015) - Sgorlon, Sandy; Fanzago, Marta; Guiatti, Denis; Gabai, Gianfranco; Stradaioli, Giuseppe; Stefanon, Bruno
Abstract Background Whether the measurement of cortisol in dairy cows can be used as a biomarker of adverse environmental or pathophysiological conditions is still under of scientific debate. In these situations, several systems mainly the hypothalamic-pituitary-adrenal axis, the autonomic nervous system, and the immune system are recruited to reestablish homeostasis. A first aim of the present study was to compare milk and blood cortisol concentrations and to consider its variability in milk in relation to farm, milk yield and days in milk. A second study investigates the effects of breed, class of somatic cell count (SCC) and farm on milk cortisol levels in a larger number of cows and farms, with the aim to validate the results obtained in the pilot study. Methods For study 1, 135 cows were sampled from 2 Italian Simmental and 2 Italian Holstein commercial farms, whilst in the second study, 542 cows were sampled from 6 commercial farms of Italian Simmental and 499 cows from 4 commercial farms of Italian Holstein. Results In study 1, the values of cortisol content in milk were significantly higher in Holstein than Simmental cows. Significant differences between farms were observed for milk and plasma cortisol concentrations. Cortisol content in milk was not correlated to plasma content in study 1 and the mean milk to plasma cortisol ratio was about 1:30. In study 2, for Holstein cows, significantly higher values of milk cortisol in comparison to Simmental cows was reported. A significant effect of class of SCC was observed, cows belonging to class 3 (SCC higher than 400.000/ml) showed the highest mean values of milk cortisol. The farm effect was significant also in the study 2, confirming the results obtained in the first study. Conclusions Milk can be considered a preferential site of sampling in dairy cows to point out short term stimulation of the hypothalamic-pituitary-adrenal axis. Further studies are needed to investigate the physiological basis of the relationship between milk cortisol content and breed, milk yield and SCC to ascertain the relevance of milk cortisol to monitor the healthy status of mammary gland.